Educational Memory of Chinese Female Intellectuals in Early Twentieth Century - Jiang, Lijing (Springer Singapore, 2018)
This book studies three female Chinese intellectuals in the first half of the 20th century, namely Feng Yuanjun, Lu Yin, and Cheng Junying, the first graduates of Beijing Female Higher Normal College, which was the first-ever national higher educational institution for women in modern China. Combining narrative inquiry, life history, oral history, and psychohistory methods, it comprehensively explores the specific developmental paths and mental processes of the post-May Fourth female intellectuals, and examines the complex interrelationships between various factors including social, academic, gender, and educational evolution in the first half of the 20th century, and the emergence of modern Chinese female intellectuals. The book is highly recommended for all scholars, undergraduate and graduate students of modern Chinese history, gender and women's studies, history of education, history of higher education, etc., and for all those who are interested in female Chinese intellectuals.